E-cigarette, cigarette, and cannabis use patterns as a function of sexual identity in a sample of Southern California young adults. (June 2021) - Liautaud, Madalyn M.; Barrington-Trimis, Jessica L.; Liu, Feifei; Stokes, Andrew; Krueger, Evan A.; McConnell, Rob; Pang, Raina D.
Highlights: E-cigarettes were the most commonly used product across the lifetime. Bisexual (vs. straight, lesbian/gay) individuals had higher odds of cigarette, e-cigarette, and cannabis use. Bisexual (vs. straight) females had higher odds of lifetime cigarette use. Abstract: Purpose: Sexual minority young adults report greater cigarette and cannabis use. Emerging evidence suggests this trend may extend to e-cigarettes. The current study evaluated the relationship between sexual identity and prevalence of e-cigarette, cigarette, and cannabis use and whether such associations differ by gender. Methods: Cross-sectional, regionally representative data of young adults ( M [ SD ]age  = 20.02 [0.60] years; n heterosexual  = 1314; n bisexual  = 77; n lesbian/gay  = 28) from Wave III (2016) of the Southern California Children's Health Study were analyzed in 2019. Logistic regression analyses were conducted with sexual identity as the predictor and product use (never, prior, infrequent past 30-day [1-2 days], frequent past 30-day [3-5+ days]) as the outcome in separate models by substance (e-cigarettes, cigarettes, cannabis). Results: Bisexual individuals were the highest-risk sub-group for nearly all outcomes, with over five times the odds of reporting frequent past 30-day use for e-cigarettes (Odds Ratio [OR]: 6.68; 95% Confidence Interval [CI]: 2.80, 15.9), cigarettes (OR: 5.42; 95% CI: 2.37, 12.4), and cannabis (OR: 8.43; 95% CI: 4.40, 16.1) compared to heterosexual individuals. Although the sample size for lesbian/gay participants was small, bisexual (vs. lesbian/gay) participants also had greater odds of reporting prior use of nicotine products and frequent past 30-day cannabis use. A significant sexual identity × gender interaction emerged for lifetime cigarette use, wherein bisexual (vs. heterosexual) identity was only associated with greater odds of use for females ( p  < .01). Conclusions: Sexual minority-related disparities in substance use among young adults appear to generalize to e-cigarettes, with bisexual young adults exhibiting especially high profiles of risk.